2014
DOI: 10.1002/pro.2482
|View full text |Cite
|
Sign up to set email alerts
|

Measuring membrane protein bond orientations in nanodiscs via residual dipolar couplings

Abstract: Membrane proteins are involved in numerous vital biological processes. To understand membrane protein functionality, accurate structural information is required. Usually, structure determination and dynamics of membrane proteins are studied in micelles using either solution state NMR or X-ray crystallography. Even though invaluable information has been obtained by this approach, micelles are known to be far from ideal mimics of biological membranes often causing the loss or decrease of membrane protein activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 38 publications
2
40
0
2
Order By: Relevance
“…In short, nanodisc assemblies were prepared by using established procedures4, 5, 25 based on the production and purification of MSPΔ H 5 proteins mixed with DMPC. MLVs consisting of DMPC were prepared through a standard freeze–thaw procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, nanodisc assemblies were prepared by using established procedures4, 5, 25 based on the production and purification of MSPΔ H 5 proteins mixed with DMPC. MLVs consisting of DMPC were prepared through a standard freeze–thaw procedure.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of membrane protein dynamics in micelles and nanodiscs revealed that micelles compromised the inherent flexibility of the protein, despite conservation of the structure 21, 28. Recent investigations into membrane proteins4, 19, 22, 25 have revealed that nanodiscs are a suitable tool to reconstitute membrane proteins in a native environment to solve their three‐dimensional structure with atomic resolution. They are derived from apolipoprotein A1 (ApoA‐1), which solubilises hydrophobic molecules, such as lipids and cholesterol, to deliver them to the liver through the blood and interstitial fluid as high‐density lipoprotein (HDL) particles 16, 27.…”
Section: Introductionmentioning
confidence: 99%
“…In short, nanodisc assemblies were prepared by using established procedures [4,5,25] based on the production and purification of MSPDH5p roteinsm ixed with DMPC.MLVsconsisting of DMPC were prepared throughastandard freeze-thaw procedure. Solid-state NMR spectroscopy is at echnique that is not restricted by the size of nano-objects and NMR spectroscopy measurements reported herein were performed on intact nanodiscs and vesicles, without the use of sonication, detergents or organic solvents to solubilise the lipid assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…[11,36] Ac omparison of membrane protein dynamics in micellesa nd nanodiscs revealed that micelles compromised the inherentf lexibility of the protein, despite conservation of the structure. [21,28] Recent investigations into membrane proteins [4,19,22,25] have revealed that nanodiscs are as uitable tool to reconstitute membrane proteins in an ative environmentt o solve their three-dimensional structure with atomic resolution. They are derived from apolipoprotein A1 (ApoA-1), whichs olubilisesh ydrophobic molecules,s uch as lipids and cholesterol, Nanodiscs offer av ery promising tool to incorporate membrane proteins into native-like lipid bilayers and an alternative to liposomest om aintain protein functions and protein-lipid interactions in as oluble nanoscale object.…”
Section: Introductionmentioning
confidence: 99%
“…The most rigorous and compelling study came from Wagner’s group, where they solved the structure of a beta barrel protein, OmpX, in nanodiscs using small discs formed by the ΔH5 deletion construct of MSP [25]. A later study performing RDC measurements of OmpX nanodiscs carried out using Pf1 phage alignment medium, has helped better define the orientation of N-H bonds thereby improving the overall structure of OmpX in ΔH5 discs [50]. …”
Section: Application Of Nanodiscs For Structural Studies By Solution Nmrmentioning
confidence: 99%